A Marxist ecocritical analysis of the songs of the Salidummay Cultural Group from their albums Salidummay, Elalay, Dongdong-ay, Diway, Ay-ay Salidummay and Chuwassi - Calabias, Jose Kervin Cesar
This study contributes to the discourse of Marxist-ecocriticism that combines classical and neo-Marxist theories with ecocriticism. As a literary hermeneutic, this has been deployed to the songs of the Salidummay Cultural Group. In analysing the poetics and politics of the songs, the people's perspective has been forwarded. The people's perspective through the people's art provides an alternative understanding to the discourse of climate change and the environment in the Cordillera -- Author's abstract.